Analysis of Consumer Intention to Use BPD Bali Bank QRIS Payment Technology Using the Technology Acceptance Model Approach at the Denpasar Festival UMKM Exhibition - Ni Made Novi Karina; I Putu Wahyu Dwinata; Ni Putu Siska Pratiwi; Ni Kadek Ayu Mirah Heni (Philippine Social Science Journal, 2025)
To align with the digital transformation of MSMEs, Bank BPD Bali integrated QRIS into its mobile platform. This study utilized a descriptive survey to analyze consumer adoption of this system at the Denpasar Festival, specifically examining brand trust, perceived usefulness, and ease of use. Results indicate that these factors significantly enhance user attitudes, which in turn drive the behavioral intention to use QRIS. These findings demonstrate that regional banks can compete with national players by offering robust, convenient digital payment solutions that prioritize customer security. Future research should investigate the environmental sustainability of such systems and their specific adoption trends among Generation Z.